Study of Theory and Technology of Exponential Function in Senior High School based on Practseology Organization - Fatikha Hanum Islahia; Dyana Wijayanti; Nila Ubaidah (Hipotenusa : Journal of Mathematical Society, 2020)
The purpose of this study was to determine the change in exponential function material in the KBK 2004 curriculum   textbooks up to the 2013 revised 2017 curriculum in Indonesia in a study of theory and technology and based on reference to the epistemological model of exponent functions containing pre-psychological organisation. The data source was taken from the mathematics handbook of class XII IPA for KBK 2004 curriculum and KTSP 2006 curriculum, the BSE math class XII book for 2013 curriculum until the 2013 revised 2016 curriculum and the mathematics module specialization book for class X for the 2013 revised curriculum 2017. Data analysis techniques used by researchers were divided into 4, namely coding, categorizing, comparison, discussion. The results of research that has been done, researchers have found the presentation of exponential function theory with 5 core categories of understanding. In theoretical studies, the 2013 revised 2016 curriculum mathematics textbook has a more complex theory and is in accordance with the reference epistemological models. While technology studies have math books, there are more complex technologies, namely the 2013 revised 2014 curriculum mathematics textbooks, there is the first form of technology and in the 2013 revised 2017 curriculum mathematics textbooks and the 2016 revised 2013 curriculum mathematics textbooks, there is a third form of technology textbooks and the curriculum mathematics textbooks 2006 (KTSP 2006) there is a third form of technology.